ANALISIS UNSUR INTRINSIK CERITA RAKYAT OIL LELANG (SULTAN NAJJAMUDIN) DARI DESA HULNANI - Luthfiyah R.A Tonu; Marselus Robot; Karolus B. Jama (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
This study aims to identify and describe the intrinsic elements of the folklore